Evidence that meniscus damage may be a component of osteoarthritis: the Framingham study - Englund, Martin; Haugen, I. K.; Guermazi, Ali; Roemer, Frank; Niu, J.; Neogi, T.; Aliabadi, P.; Felson, D. T. (Osteoarthritis and Cartilage, 2016)
The etiology of degenerative meniscus tear is unclear but could be related to a generalized osteoarthritic disease process. We studied whether radiographic hand osteoarthritis (OA) is associated with meniscus damage.We examined 974 persons aged 50-90 years drawn via census tract data and random-digit dialing from Framingham, Massachusetts, United States. One reader assessed bilateral hand radiographs (30 joints) and another read frontal knee radiographs, all according to the Kellgren-Lawrence (KL) scale. A third reader assessed right knee 1.5-T magnetic resonance imaging (MRI) scans for meniscus damage. We calculated the prevalence of medial and/or lateral meniscus damage in those with one to two and three or more finger joints with radiographic OA (KL grade >=2) compared to those without radiographic hand OA with adjustment for age, sex, and body mass index. We also evaluated the above association in persons without evidence of radiographic OA (KL grade 0) in their knee (n = 748).The prevalence of meniscus damage in the knee of subjects with no, one to two, and three or more finger joints with OA was 24.9%, 31.7%, and 47.2%, respectively. The adjusted prevalence ratio (PR) of having meniscus damage was significantly increased in those who had three or more finger joints with OA (1.40 [95% confidence interval (CI) 1.11-1.77]). The estimate remained similar in persons without evidence of radiographic OA in their knee (PR, 1.42 [95% CI 1.03-1.97]). The association was more robust for medial meniscus damage.Results suggest a common non-age related etiologic pathway for both radiographic hand OA and meniscus damage.
EVALuna2:14472